Exploring the relationship between older adults’ online health information seeking, negative emotions and prevention behaviors in the pandemic context: a two-wave longitudinal study - Liu, Tianchang; Song, Xiaokang; Zhu, Qinghua (Frontiers in Public Health, 2024)
During the COVID-19 pandemic, older adults were facing more mental health issues that may cause complex impacts on pandemic prevention, and turning to the internet for health information is a double-edged sword for them. This study aimed to investigate the reciprocal relationship between negative emotions and prevention behaviors in older adults, as well as the direct and moderating effects of online health information seeking (OHIS) on negative emotions and prevention behaviors. [Methods]: Based on the common-sense model of self-regulation (CSM) and a sample of more than 20,000 participants from the Survey of Health, Aging and Retirement in Europe (SHARE), this study first used an autoregressive cross-lagged panel model (CLPM) to analyze the longitudinal effect of negative emotions on prevention behaviors. Second, the study used ordinary least squares (OLS) regression to explore the influence of OHIS usage frequency changes on negative emotions and prevention behaviors. Third, the study used multigroup analysis to examine the moderating effect of OHIS usage frequency changes on the CLPM. [Results]: The findings indicate a significant longitudinal association where initial negative emotions predicted later prevention behaviors (β = 0.038, p < 0.001), and increased OHIS frequency was linked to positive changes in prevention behavior (β = 0.109, p < 0.001). Multigroup analysis revealed that the connection between negative emotions or increased negative emotions and prevention behaviors remained significant for those with no change or an increase in OHIS frequency but not for those with a decrease. [Conclusions]: This study suggested that negative emotions may drive older adults to engage more in prevention behaviors and that OHIS can augment this effect. These results underscore the importance of addressing mental health and providing reliable online health information to support older adults in managing infectious disease risks.